2020
DOI: 10.1093/braincomms/fcaa034
|View full text |Cite
|
Sign up to set email alerts
|

Welcoming back my arm: affective touch increases body ownership following right-hemisphere stroke

Abstract: Right-hemisphere stroke can impair the ability to recognize one’s contralesional body parts as belonging to one’s self. The study of this so-called ‘disturbed sense of limb ownership’ can provide unique insights into the neurocognitive mechanisms of body ownership. In this study, we address a hypothesis built upon experimental studies on body ownership in healthy volunteers. These studies have shown that affective (pleasant) touch, an interoceptive modality associated with unmyelinated, slow-conducting C-tacti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 79 publications
1
16
0
Order By: Relevance
“…This supports the idea that sensory information plays a crucial role in bodily self, as shown by studies on deafferented people, in particular individuals suffering from spinal cord injury (SCI; Scandola et al, 2014 , 2017a , 2019b ; Moro et al, 2021a ) or locked-in-syndrome ( Nizzi et al, 2012 ), and recently confirmed by the effects of interoceptive modulations on the sense of body ( Salvato et al, 2017 ; Jenkinson et al, 2020 ; Monti et al, 2020 ; Todd et al, 2021 ).Thus, representations underlying bodily self are the result of a continuous integration of multiple sources of information. This integration process provides immediate feedback on the current state of the body and is also integrated with higher-order cognitive functions (e.g., spatial perception and memory) in order to obtain a detailed map of the body and its relationship with the environment in terms of action planning and motor imagery.…”
Section: Introductionsupporting
confidence: 83%
“…This supports the idea that sensory information plays a crucial role in bodily self, as shown by studies on deafferented people, in particular individuals suffering from spinal cord injury (SCI; Scandola et al, 2014 , 2017a , 2019b ; Moro et al, 2021a ) or locked-in-syndrome ( Nizzi et al, 2012 ), and recently confirmed by the effects of interoceptive modulations on the sense of body ( Salvato et al, 2017 ; Jenkinson et al, 2020 ; Monti et al, 2020 ; Todd et al, 2021 ).Thus, representations underlying bodily self are the result of a continuous integration of multiple sources of information. This integration process provides immediate feedback on the current state of the body and is also integrated with higher-order cognitive functions (e.g., spatial perception and memory) in order to obtain a detailed map of the body and its relationship with the environment in terms of action planning and motor imagery.…”
Section: Introductionsupporting
confidence: 83%
“…When VLSM results were calculated with the permutated (number of permutations set to 1000) Brunner-Menzel test to correct for multiple comparison and small sample size and using a minimum 10% patient threshold (Rorden et al, 2007), no significant results were obtained. This is not uncommon in similar studies with small sample sizes, large lesions in the patient groups and relatively small variance in the experimental scores (see Jenkinson et al, 2020). An exploratory VLSM analysis was therefore run, using less restrictive criteria (i.e.…”
Section: Lesion Analysesmentioning
confidence: 80%
“…Nowadays, such findings make sense in terms of affective touch (stroking) leading to greater incorporation of the seen body into the body image. In such cases, note, the type of touch (affective or not) modulates the extent of vision's dominance over proprioception, and thus bodily incorporation (Jenkinson, Papadaki, Besharati, Moro, Gobbetto, Crucianelli, et al, 2020;Panagiotopoulou, Filippetti, Tsakiris, & Fotopoulou, 2017; though see also Spaccasassi, Frigione, & Maravita, 2021).…”
Section: Visual Contributions To Affective Touchmentioning
confidence: 99%